2021
DOI: 10.7150/thno.58380
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase B regulates macrophage metabolism in the tumor microenvironment

Abstract: Background : Glucose metabolism in the tumor-microenvironment is a fundamental hallmark for tumor growth and intervention therein remains an attractive option for anti-tumor therapy. Whether tumor-derived factors such as microRNAs (miRs) regulate glucose metabolism in stromal cells, especially in tumor-associated macrophages (TAMs), to hijack them for trophic support, remains elusive. Methods : Ago-RIP-Seq identified macrophage lactate dehydrogenase B (LDHB) as a target of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…The crosstalk between tumor cells and macrophages is affected by microRNAs (miRNAs). Tumor-derived factor miRNAs, a kind of small non-coding RNA, can regulate target gene expression after transcription [ 122 ] ( Figure 4 A). According to reports, miRNA dysregulation can induce the occurrence of a variety of malignant tumors, and it has a significant impact on tumor immune escape, invasion, angiogenesis, migration and drug resistance [ 123 , 124 ].…”
Section: Macrophages In Tumor Therapymentioning
confidence: 99%
“…The crosstalk between tumor cells and macrophages is affected by microRNAs (miRNAs). Tumor-derived factor miRNAs, a kind of small non-coding RNA, can regulate target gene expression after transcription [ 122 ] ( Figure 4 A). According to reports, miRNA dysregulation can induce the occurrence of a variety of malignant tumors, and it has a significant impact on tumor immune escape, invasion, angiogenesis, migration and drug resistance [ 123 , 124 ].…”
Section: Macrophages In Tumor Therapymentioning
confidence: 99%
“…and Frank et al. have also found that LDH can recruit and regulate tumor-associated macrophage metabolism in breast cancer to affect breast cancer cell proliferation and invasion ( 20 , 35 ). Ruiz-Rodado et al.…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of excessive metabolism of tumor cells, LDH promotes the tumor-specific Warburg effect; this produces energy and lactic acid through glycolysis, which is involved in the tricarboxylic acid cycle after being re-ingested by cancer cells (34). Wang et al and Frank et al have also found that LDH can recruit and regulate tumor-associated macrophage metabolism in breast cancer to affect breast cancer cell proliferation and invasion (20,35). Ruiz-Rodado et al demonstrated that the glioma IDH1-mut invasive cell line obtained a high glycolysis phenotype through the specific deletion of methylation of the LDH promoter, which was associated with a worse survival rate (36).…”
Section: An Increasing Number Of Studies Have Indicated That Tumorigenesis Is Closely Associated With Abnormalities In Thementioning
confidence: 99%
“…Lactate dehydrogenase B (LDHB) is a glycolysis-related enzyme that catalyzes the interconversion of pyruvate and lactate, whose function in macrophages has been poorly investigated [59]. Frank et al demonstrated that miR-375 derived from breast cancer cells is captured by TAMs, where it reduces LDHB expression levels, likely by directly targeting its transcript.…”
Section: Non-coding Rnas In the Regulation Of Bc Cells And Tam Metabo...mentioning
confidence: 99%
“…The increased production of lactate and sterol by TAMs in the TME boosts tumor progression by stimulating cancer cell proliferation and survival. Therefore, miR-375 can be a promising target to selectively interfere with TAM tumor-promoting functions by reverting their metabolic status [59].…”
Section: Non-coding Rnas In the Regulation Of Bc Cells And Tam Metabo...mentioning
confidence: 99%